2017
DOI: 10.1055/s-0043-110668
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic hand-suturing for defect closure after gastric endoscopic submucosal dissection: a pilot study in animals and in humans

Abstract: Mucosal suturing enables reliable and optimal defect closure after endoscopic treatments. We developed and investigated the feasibility of endoscopic hand-suturing (EHS) after gastric endoscopic submucosal dissection (ESD) in porcine in vivo models and in human clinical cases. EHS involving continuous suturing of the mucosal layers using a through-the-scope needle-holder and absorbable barbed suture, was performed after gastric ESD in six live pigs and in eight consecutive patients. Success rates, adverse even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 17 publications
0
51
0
Order By: Relevance
“…The unsustained closure occurred possibly because of insufficient tightening of the suture due to difficult needle manipulation in retroflexion, and poor approximation of the defect edges near the anal verge given the surrounding connective tissue outside the rectal lumen. Second, we used a single-channel colonoscope during EHS of the colorectum even in the distal colon, whereas a double-channel gastroscope was used in the stomach in the Goto study [19]. Needle grasping and releasing were easier when both accessory channels were utilized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unsustained closure occurred possibly because of insufficient tightening of the suture due to difficult needle manipulation in retroflexion, and poor approximation of the defect edges near the anal verge given the surrounding connective tissue outside the rectal lumen. Second, we used a single-channel colonoscope during EHS of the colorectum even in the distal colon, whereas a double-channel gastroscope was used in the stomach in the Goto study [19]. Needle grasping and releasing were easier when both accessory channels were utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Goto et al developed endoscopic hand-suturing (EHS) to close large mucosal defects after ESD. A former pilot study demonstrated technical feasibility and sustained closure of mucosal defects after gastric ESD [19]. However, there are no data regarding the clinical use of EHS for defect closure after colorectal ESD.…”
Section: Introductionmentioning
confidence: 99%
“…showed that endoclip closure of post‐ESD ulcer significantly reduced delayed bleeding rate compared to the control group (3.3% vs 13.3%, P = 0.04). There were small case series suggesting the usefulness of endoscopic closure of the post‐ESD ulcer using endoclip‐and‐loop, OTSC device, overstitch suturing, or hand‐sewn suturing, although they were not comparative studies.…”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
“…EHS was performed using a GIF-Y0080 3D scope (Olympus) equipped with a prototype flexible needle holder (Olympus) and 15-cm, 3-0 absorbable barbed V-Loc 180 (VLOCL0604) sutures (Covidien, Mansfield, MA, USA), as described elsewhere. 1,2 Briefly, a needle with a knot at the tail was inserted from the markings on the right row and pulled out from the markings on the left row (Supplementary video 1), and the sutures were placed continuously and linearly from the distal to the proximal side (Fig. 1B).…”
Section: Endoscopic Hand Suturing Settings and Proceduresmentioning
confidence: 99%
“…Endoscopic hand suturing (EHS) is a novel suturing method that allows optimal and secure intraluminal suturing. 1,2 In EHS for mucosal defects, the mucosal rim of the defect is continuously and linearly sutured using a transorally delivered needle and suture. Although EHS is expected to be a promising technique for the development of various advanced therapeutic endoscopies, it requires advanced technical skills and significant experience in puncturing the mucosa using the needle, optimally grasping the needle, and tightening the thread using a flexible endoscope; therefore, how to efficiently obtain these necessary skills is an issue to be addressed.…”
Section: Introductionmentioning
confidence: 99%